Colonial Modernity and Diffusion of Power: Identity and Community Formation among Mappilas of Malabar - T.A, Shameer (Method & theory in the study of religion, 2022)
This paper explores colonial modernity and the knowledge system’s role in constituting community formation among the Mappilas of Malabar. Colonial modernity, such as the introduction of printing, made this transformation more advanced and communitarian in structure. It also discusses colonialism as a force to reshape and bring socio-cultural changes in Malabar during the time. It argues that the existence of a clearly defined community is not a predetermined social fact; it looks at how the Mappilas were represented in an analytical category. In Malabar, the press and literature have played an essential role in framing community consciousness among Mappila society. Print media has brought a revolution in the transmission of knowledge. This paper will encompass the coming of the printing press and the moulding of community consciousness among the Mappilas of Malabar. It discusses the discursive and non-discursive practices of the colonial state for constructing various identities in Malabar.